Study of Atmospheric Corrosion of Structural Steel Surrounding the Palm Oil Industry in the Region of Eastern Coastal and Northern Aceh - Cut, Banta; Muhammad Zulfri; Syarizal Fonna; Syifaul Huzni; Ferry Safriwardy; Abdul Rahman; Budi Istana (SURYA TEKNIKA, 2024)
Corrosion is the primary cause of premature infrastructure damage, affecting everything from homes and public spaces to industrial facilities, including the rapidly expanding palm oil industry in Aceh, particularly along its eastern and northern coasts. This rapid growth necessitates careful consideration of environmental impacts, including pollution, which can also degrade air quality. Pollutants increase the susceptibility of steel-reinforced structures to atmospheric corrosion. This research, therefore, investigates atmospheric corrosion of structural steel at several palm oil processing plants: PTPN 1 Tanjung Seumantoh in Aceh Tamiang, PT Ensem Sawita and PT Anugerah Fajar Rejeki (AFR) in East Aceh, and PTPN 1 Cot Girek in North Aceh.This study measures the atmospheric corrosion rate of structural steel typically used in industrial and nearby residential settings. Five steel types were tested: strip, angular, cylindrical, commercial plate, and low-carbon steel. Following the American Standard Testing and Material-G50 (ASTM G50), the mass loss method was used to calculate corrosion rates. After six months of exposure, all five steel types exhibited corrosion rates below 0.7 mils per year (mpy). This result showed that the relative corrosion resistance of structural steel is on outstanding category (<1mpy).